The Mozart effect : tapping the power of music to heal the body, strengthen the mind, and unlock the creative spirit - Campbell, Don G., 1946-2012. 4 0; 5 (Australia : Hodder & Stoughton, 1997)
The Mozart Effect offers dramatic accounts of how doctors, shamans, musicians, and healthcare professionals use music to deal with everything from anxiety to cancer, high blood pressure, chronic pain, dyslexia, even mental illness. Students who sing or play an instrument score up to 51 points higher on SATs that the national average. During childbirth, music can relieve expectant mothers' anxiety and help release endorphins, the body's natural painkillers, dramatically decreasing the need for anesthesia. The director of a Baltimore hospital's coronary care unit says that half an hour of classical music produces the same effect as ten milligrams of Valium. And now, whatever your listening taste, Don Campbell explains how to make the Mozart Effect work for you. Drawing on medicine, Eastern wisdom, and the latest research on learning and creativity, Campbell reveals how exposure to sound, music, and other forms of vibration, beginning in utero, can have a lifelong effect on health, learning, and behavior. He shows how to use sound and music to stimulate learning and memory; how to strengthen listening abilities; how to use imagery to enhance the Mozart Effect; and how to harness the power of toning, chanting, mantras, rap, and other self-generated sounds. He lists fifty common conditions, ranging from migraines to substance abuse, for which music can be used as treatment or cure. And he recommends more than two dozen specific, easy-to-follow exercises to help you raise your spatial IQ, sound away pain, boost creativity, and make the spirit sing.--Jacket
The speech of angels and atoms -- A healing breeze of sound -- Sound beginnings : the Mozart effect -- Sound listening : the anatomy of sound, hearing, and listening -- Sound healing : the healing properties of sound and music -- Sound voice : your original healing instrument -- Sound medicine : using music for therapy and rehabilitation -- Sound images : orchestrating the mind and body -- Sound intellect : enhancing learning and creativity with music -- Sound spirit : the bridge between life and death -- The eternal song -- Miracle stories of treatment and cure
Includes bibliographical references (pages 293-321) and index
Keywords: 2 -- 0; 6; Music therapy;Music Therapy -- 20; 20; 2